As relações entre a concepção de natureza de F. Engels e a hipótese A. I. Oparin sobre o problema da origem da vida na terra - Negretti, Carlos (2006)
The Russian biochemist Alexandre Ivanovicth Oparin , in 1924 in the former Soviet Union wrote an article in which he puts forward his hypothesis about a delicate subject in the history of biology: the origin of life on Earth. Proposes his hypothesis about th origin of life relating the biological evolution mainly the Natural Selection Theory of Charles Darwin with the Dialectic Materialism of Karl Marx and Friedrich Engels. There are some disagreements about the nature of such relation, which is considered by some authors coherent and by others just adequate to political pressures of the Stanilist regime in the former Soviet Union. From a comparative analysis between the books of Engels mainly Dialectic of Nature, in with his conception of nature and dialectic materialism are present and Oparin s articles, this work shows that such concepts helped Oparin to develop his lage hypothesis with a sophistication in terms of argument, to the philosophical point of view as well as experimental